ANALISIS PEMASARAN PADI SAWAH DI DESA KEMUNING MUDA KECAMATAN BUNGARAYA KABUPATEN SIAK - Evy Maharani; Susy Edwina; Sopan Sujeri (Fakultas Pertanian, Universitas Riau, 2015)
The agricultural sector has a very important meaning in determining the formation of various economic and social realities in different regions of Indonesia. Potential agricultural sector developed in Indonesia one of which is a sub-sector of food crops, especially rice plants. This study aimed to analyze the marketing of paddy in the village of Kemuning Muda District of Bungaraya Siak. This research was conducted in Desa Kemuning Muda District of Bungaraya in January 2015. Young Desa Kemuning village has a land area and highest rice producer in Sub Bungaraya. The results showed the marketing of paddy in the village of Kemuning Muda there are two marketing channels. In the marketing channel I includes paddy rice farmers, rice mills employer, and the final consumer. Marketing channel II includes paddy rice farmers, millers employer, retailers, and end customers. Marketing functions performed by marketing agencies include exchange function, physical function and function facilities or facilitating function. The highest marketing margin is the marketing channel II amounted to 10.89 percent. The most efficient marketing channel I with the efficiency of 3.89 percent.